Financial Distress Analysis in Media and Entertainment Companies: The Role of Liquidity, Leverage, Profitability, and Firm Size - Rizki Kurniawan; Witjaksono Eko Hartoto (Universitas Negeri Semarang, 2026)
The study aims to determine and assess the size, profitability, leverage, and liquidity of corporations in relation to the financial difficulties of media and entertainment firms listed on the Indonesia Stock Exchange, which saw a fall in earnings between 2021–2024. This study's population was 56 randomly selected samples of secondary data extracted from yearly financial reports. Multiple linear regression was used for the study. The analysis of the data shows that, partially, there is a positive effect of the liquidity variable (CR), a negative effect of the leverage variable (DER), a positive effect of the profitability variable (ROA), and a negative effect of the company size variable. At the same time, 31% of the variance in financial distress is attributable to factors outside the scope of this investigation, while 69% is attributable to the interplay between liquidity, leverage, profitability, and firm size.